Предмет: Математика,
автор: sunshine52
решите уравнение:
а*(а-3)+2а-6=0
Ответы
Автор ответа:
33
а × ( а - 3 ) + 2а - 6 = 0
а² - 3а + 2а - 6 = 0
а² - а - 6 = 0
D = 1 - 4 × 1 × (-6) = 1 + 24 = 25 > 0. 5.
х1 = 1 + 5 / 2 = 6/2 = 3.
х2 = 1 - 5 / 2 = -4/2 = -2.
Ответ : -2 ; 3.
_______________________________
Удачи)))))
а² - 3а + 2а - 6 = 0
а² - а - 6 = 0
D = 1 - 4 × 1 × (-6) = 1 + 24 = 25 > 0. 5.
х1 = 1 + 5 / 2 = 6/2 = 3.
х2 = 1 - 5 / 2 = -4/2 = -2.
Ответ : -2 ; 3.
_______________________________
Удачи)))))
Автор ответа:
5
a^2-3a+2a-6=0
a^2-a-6=0
a^2-a=6
a^2-a+(1/2)^2=6+(1/2)^2
(a-1/2)^2=25/4
a=-2 ; a=3
a^2-a-6=0
a^2-a=6
a^2-a+(1/2)^2=6+(1/2)^2
(a-1/2)^2=25/4
a=-2 ; a=3
Похожие вопросы
Предмет: Информатика,
автор: daha2003712
Предмет: Математика,
автор: lerka13122006
Предмет: Литература,
автор: matveykolyshkin08
Предмет: Математика,
автор: mskuzkat20050
Предмет: Литература,
автор: ialexanderpol